A new approach to modelling of seasonal soil temperature fluctuations and their impact on the performance of a shallow borehole heat exchanger. (December 2020) - Sofyan, Sarwo Edhy; Hu, Eric; Kotousov, Andrei; Indra Riayatsyah, Teuku Meurah; Khairil; Hamdani
Abstract: A borehole heat exchanger (BHE) could be used in heating and cooling systems as the ground temperature is normally higher than the average air temperature in winter and lower in summer. This difference in the temperature can be used to improve the efficiency of air conditioning systems (in summer) and heat pumps (in winter). The performance of a BHE is influenced by soil temperature that may have significant seasonal changes. These changes were largely ignored in previous BHE modelling approaches being a source for large errors in theoretical predictions. This paper presents a new internal source term approach to account for the (seasonal) fluctuation in soil temperature on a shallow BHE's performance. The proposed model is able to consider the heat flow in multi-ground-layers. The governing equations of the model are solved by using explicit finite different method. The model is validated using experimental data. The simulated soil temperatures with and without the internal heat source term showed that the maximum relative errors are 3.7% and 14% respectively. The use of high thermal conductivity grout resulted in a decrease in the borehole thermal resistance. The outlet fluid temperature under the continuous operation mode is higher than that operated under the intermittent mode.